DYNAMICAL STABILITY EVALUATION OF THE MILLING THROUGH ROUGHNESS PROFILES ANALYSIS - Sánchez Hechavarría, Y.; Mariño Cala, M. (Nexo Revista Científica, 2016)
The objective of this research is to carry out the evaluation of the dynamic stability of inclined surface milling process of the hardened steel AISI D6 with high speeds, through the analysis of the roughness profiles in the sense of the advance. The evaluation of the dynamic stability was based in the analysis of the roughness profiles, the signal of the force component in the axis Y in time domain and the Root Mean Square of the signals of force in the three axes. The research demonstrated that it is possible to evaluate the dynamic stability of a milling process through the analysis of the roughness profiles, being obtained profiles uniforms and smaller values of superficial roughness in the most stable processes. It was also demonstrated that the roughness and the superficial quality depend in bigger measure of the dynamic stability of the process that of the cutting speed, being achieved in areas of more dynamic stability, to increase the advance speed and cut with good results in the superficial roughness of the milled piece.